PENGARUH KEGIATAN FASHION SHOW TERHADAP KEPERCAYAAN DIRI PADA ANAK USIA 5-6 TAHUN DI PAUD AQILA KIDS RIMBO PANJANG KECAMATAN TAMBANG KABUPATEN KAMPAR - Wardoyo, Anita; Zulirfan, Zulirfan; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the result of observation in the field toward confidence of student, it find that confidence of student are not yet improve optimally. So, there is needed applying of fashion show activity. This research has a purpose to know the influence of fashion show activity. This research of applying fashion show activity toward confidence of 5-6 years old children in early childhood Aqila Kids District Tambang Regency of Kampar. Sample of this research are 14 student of class B. Technique to college data is using observation technique and technique of data analysis is using t-test with using SPSS 18.0 program. Hypotheses of this research is there are very significant influence toward student confidence after applying fashion show activity. This is knowing from the result of data obtained t=17.298 p=0,000 because p < 0,05. So, it can be conclude that there has a very significant different of student confidence. confidence after using fashion show activity in teaching learning. So, its mean that Ho refused and Ha accepted that means there are very significant different between before and after doing the experiment with fashion show activity. The effect of fashion show activity to confidence of 5-6 years old children at early childhood Aqila Kids District Tambang Regency of Kampar e as much as 32,5%Keywords : Confidence, Fashion Show Activity